The Difference of Commentators and their Reasons for Al-Mawsili as a Model - Taha , Maysoon; Majeed, Ammar (Islamic Sciences Journal, 2023)
Praise be to Allah, Lord of the Worlds, and may blessings and peace be upon our Master Muhammad and upon his family and companions, and afterwards. The research is entitled (The difference of the commentators and its causes Al-Mawsili as a model) . The researcher explained the meaning of the difference, its types, and its causes, and considered it a difference of the praiseworthy type that the Majestic and Exalted had envisaged, which opened the door for researchers to benefit from the possible meanings of words and compositions over time and ages. The research presented a number of reasons for differing commentators, and they are nothing more than technical, linguistic, customary or legal differences. As for the interpretations of those with whims and fads, they are rejected, because they used the Qur’anic texts as justification for their meanings to achieve their goals or partisan, sectarian or national interests. That is what you find in this study, Allah Almighty willing.